Closure of non-healing perianal Crohn’s disease with surgery and vacuum-assisted closure (VAC) system - Uzun, Orhan; Dinçer, Mürşit; Senger, Aziz Serkan; Değer, Kamuran Cumhur; Duman, Mustafa (Turkish Journal of Gastroenterology, 2018)
Abstract Cite this article as: Uzun O, Dinçer M, Senger AS, Değer KC, Duman M. Closure of non-healing perianal Crohn’s disease with surgery and vacuum-assisted closure (VAC) system. Turk J Gastroenterol 2018; 29: 367-9.